2018
DOI: 10.1080/16549716.2019.1663619
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequality and adolescent suicide ideation across Africa, Asia, the South Pacific and Latin America – a cross-sectional study based on the Global School Health Survey (GSHS)

Abstract: Background: Suicide ideation is a health issue affecting adolescents worldwide. There are significant variations in suicide ideation between countries and genders, which have not been fully explained. Research is especially lacking in countries outside Europe and North America. Gender equality has been shown to matter in other aspects of adolescent mental health, such as life satisfaction, but has not been researched in relation to suicide ideation at national level. Objective: To investigate how national gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In a study of young people aged 10 to 24 years from 21 Latin American and Caribbean countries using the WHO-CDC Global School Health Survey (GSHS), Elia et al [ 35 ] found a direct relationship between income and obesity, and then a direct relationship between obesity and suicide ideation with planning, suggesting that overweight/obesity might be on the causal pathway from economic disadvantage to suicide. In another study with worldwide GSHS data, Assarson et al [ 36 ] found a positive association of suicide ideation with gender inequality when controlling for income. Other studies have found a negative gradient or inverse relationship between income and suicide, in the Americas [ 20 , 37 , 38 ] and elsewhere [ 20 , 39 , 40 , 41 ], and yet other studies have described the positive gradient between suicide and income inequality rather than income level [ 37 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of young people aged 10 to 24 years from 21 Latin American and Caribbean countries using the WHO-CDC Global School Health Survey (GSHS), Elia et al [ 35 ] found a direct relationship between income and obesity, and then a direct relationship between obesity and suicide ideation with planning, suggesting that overweight/obesity might be on the causal pathway from economic disadvantage to suicide. In another study with worldwide GSHS data, Assarson et al [ 36 ] found a positive association of suicide ideation with gender inequality when controlling for income. Other studies have found a negative gradient or inverse relationship between income and suicide, in the Americas [ 20 , 37 , 38 ] and elsewhere [ 20 , 39 , 40 , 41 ], and yet other studies have described the positive gradient between suicide and income inequality rather than income level [ 37 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GSHS questionnaire is a self-reported survey conducted primarily among students between the ages of 13–17 (some students being a couple years older or younger). The samples are selected on a national or regional basis, or sometimes both combined (Assarsson et al., 2018 ; Centers for Disease Control and Prevention, 2013 ).…”
Section: Data Variables and Methodsmentioning
confidence: 99%
“…Risk ratios Suicide continues to be regarded as a substantial global health issue which carries a substantial psychological impact that affects the afflicted individuals and their families but also transcends the individual level to impact the larger family and community at economic and social levels [1][2][3][4] . The prevention of suicide has been identified as an important target for organizations tasked with the promotion of large-scale public mental health campaigns; for example, the World Health Organization's (WHO) Mental Health Action Plan has set itself the goal of reducing the incidence of suicide by at least 10% over an 8-year period 5 .…”
Section: Uae United Arab Emirates Who World Health Organization Gshs ...mentioning
confidence: 99%